If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-7d + 1) = 34 + 5d Reorder the terms: -2(1 + -7d) = 34 + 5d (1 * -2 + -7d * -2) = 34 + 5d (-2 + 14d) = 34 + 5d Solving -2 + 14d = 34 + 5d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-5d' to each side of the equation. -2 + 14d + -5d = 34 + 5d + -5d Combine like terms: 14d + -5d = 9d -2 + 9d = 34 + 5d + -5d Combine like terms: 5d + -5d = 0 -2 + 9d = 34 + 0 -2 + 9d = 34 Add '2' to each side of the equation. -2 + 2 + 9d = 34 + 2 Combine like terms: -2 + 2 = 0 0 + 9d = 34 + 2 9d = 34 + 2 Combine like terms: 34 + 2 = 36 9d = 36 Divide each side by '9'. d = 4 Simplifying d = 4
| 2x^4-9x^3-7x^2+9x+5=0 | | 3(4/5x-5) | | (3/4)(8x-4)=(2/3)(6x-9) | | 2x+2(2x-5)=104 | | w-x=xyz | | -2+11+6x=0 | | -1.90=j-4.99 | | 12h-60=250 | | x+4+2x-1=5x-3 | | X/-8-5-2 | | 3p^2+34p+11=0 | | 2.40+1.2Z-6.5=0.7 | | 7a^2+3b^2-a^2b= | | 20x^3+17x^2-3x= | | -(4+b)=-8 | | w/6=7 | | x^4+100-20x^2=0 | | 2g^2-11g+12=0 | | 12=22+n | | 5/6z=2-11/12z | | x/4.4=6.8 | | -3(h+6)=7-2(h+6) | | 5x-40+20=20 | | 10=-2-3r | | .15+y=2.85 | | 9x/14-x/7=1 | | 5(x+6)+8=7x-2(x-4) | | -2(-x-12)=-2 | | 1.75x+y=8 | | 1.5=y-3.5 | | 5/9×3/10×3/4 | | 93=3(7-3n) |